Metallic nanoparticles: synthesis, characterisation and application. (24th January 2011) - Luong, Nguyen Hoang; Long, Nguyen Ngoc; Vu, Le Van; Hai, Nguyen Hoang; Nghia, Phan; Anh, Nguyen
Colloidal sphere-like gold nanoparticles were prepared from an HAuCl4 aqueous solution by the chemical reduction method and by using X-ray irradiation, while rod-like gold nanoparticles were synthesised according to the seed-mediated growth method and by sonoelectrochemistry. Gold nanoparticles exhibit fcc structure. Sphere-like gold nanoparticles have a diameter of 20-60 nm, while rod-like gold nanoparticles have an aspect ratio of 2–4. In UV-vis spectra, the absorption bands related to surface plasmon resonance were observed. Co-Pt nanoparticles of 5-20 nm were prepared by electrochemistry, while Fe-Pt nanoparticles with a size of 5-10 nm were prepared by sonoelectrochemistry. After annealing, these magnetic nanoparticles showed a high coercivity. The gold nanoparticles were functionalised for detecting breast cancer cells.